Scale-Up of Tailor-Made Onsite Enzyme Blend From Cassava Peels for Industrial Bioethanol Production - Martison Budu; Patrick Boakye; Joseph A. Bentil (The Scientific World Journal)
Bioethanol production is one of the key alternatives for fossil fuel use due to climate change. The study seeks to upscale tailor-made onsite enzyme blends for the bioconversion of cassava peels to bioethanol in simultaneous saccharification and fermentation (SSF) process using cassava peels-degrading fungi. The starch and cellulose contents of peels were determined. The results showed significant levels of cellulose (39.78%) and starch (31.21%), indicating that cassava peels are valuable raw materials for bioethanol production. To investigate cassava-degrading microbes, Aspergillus niger demonstrated the highest enzyme activity with a diameter of zone of clearance of 16 mm. Tailor-made enzyme blends were produced with the A. niger using various substrate concentrations (1%, 3%, 5%, 8%, and 10%) of milled cassava peels at periods of 2, 4, 6, 8, and 10 days with a spore concentration of 2.1 × 105 cells/mL. The amylolytic and cellulolytic activities were determined as 4.759 U/mL and 4.265 U/mL, respectively, at 5% and 6-day optimal conditions. The enzyme blend was upscaled using three fermentation vessels, thus 0.250 L flask, 1.0 L flask, and 10 L fermenter at optimized conditions in the SSF process for bioethanol production. These optimal conditions were firstly applied to a 0.250 L flask in the SSF process, a fixed enzyme dose of 20 mL and 1.5 g of Saccharomyces cerevisiae with varying substrate concentrations of 5%, 10%, and 20% and ethanol analyzed daily for 10 days. The theoretical ethanol yields recorded were 15.64%, 16.02%, and 14.91% for 0.250, 1, and 10 volumes obtained at different fermentation days. These optimized conditions demonstrate the potential for industrial bioethanol production in Ghana.